Rapid screening and scaled manufacture of immunogenic virus-like particles in a tobacco BY-2 cell-free protein synthesis system - Armero-Gimenez, Jorge; Wilbers, Ruud; Schots, Arjen; Williams, Charles; Finnern, Ricarda (Frontiers in Immunology, 2023)
Several vaccine platforms have been developed to fight against pathogenic threats, with Virus-Like Particles (VLPs) representing a very promising alternative to traditional platforms. VLPs trigger strong and lasting humoral and cellular immune responses with fewer safety concerns and higher stability than other platforms. The use of extensively characterized carrier VLPs modified with heterologous antigens was proposed to circumvent the viral complexity of specific viruses that could lead to poor VLP assembly and yields. Although carrier VLPs have been successfully produced in a wide variety of cell-based systems, these are limited by low protein yields and protracted clone selection and optimization workflows that limit VLP screening approaches. In response, we have demonstrated the cell-free protein synthesis (CFPS) of several variants of the hepatitis B core (HBc) carrier VLP using a high-yielding tobacco BY-2 lysate (BYL). High VLP yields in the BYL system allowed in-depth characterization of HBc variants. Insertion of heterologous sequences at the spike region of the HBc monomer proved more structurally demanding than at the N-terminus but removal of the C terminal domain allowed higher particle flexibility and insert acceptance, albeit at the expense of thermal and chemical stability. We also proved the possibility to scale the CFPS reaction up to 1L in batch mode to produce 0.45 grams of the native HBc VLP within a 48-hour reaction window. A maximum yield of 820 µg/ml of assembled VLP particles was observed at the 100µl scale and most remarkably the CFPS reaction was successfully scaled from 50µl to 1L without any reduction in protein yield across this 20,000-fold difference in reaction volumes. We subsequently proved the immunogenicity of BYL-derived VLPs, as flow cytometry and microscopy clearly showed prompt recognition and endocytosis of fluorescently labelled VLPs by human dendritic cells. Triggering of inflammatory cytokine production in human peripheral blood mononuclear cells was also quantitated using a multiplex assay. This research establishes BYL as a tool for rapid production and microscale screening of VLP variants with subsequent manufacturing possibilities across scales, thus accelerating discovery and implementation of new vaccine candidates using carrier VLPs.